El control de calidad en España y Colombia. Diferencias en su filosofía - Alegre, V.; Cansario, M. (Revista ALCONPAT, 2013)
In Spain the construction "modern" quality control was born in the "Instruction EH-73" and in Colombia it is currently contemplated by the Earthquake Resistant Regulations NSR-10 in Title I: Technical supervision. Nowadays in Spain the product certification control and execution control are compulsory; a regulatory protocol (Structural Concrete Regulations EHE-08) also exists for the control of project required for residential buildings. In Colombia it is called technical supervision, mandatory in the construction of building structures whose construction area is greater than 3000 m2, regardless of its use. Where technical supervision is not required, the builder has to perform quality checks for structural materials and nonstructural. Technical supervision is performed as required by the regulations for drawing control (project), specifications control, material control, various quality control tests and execution control.